The effectiveness of management information system in decision-making - Yousef A. Baker, El-Ebiary; Syarilla Iryani, A. Saany; Salameh A., Mjlae (2020)
Management Information System (MIS) is the use of information technology, people, and business processes to record, store and process data to produce datadriven information that helps managers to derive decisions for the organizations. The decision is consciously taken from a variety of alternatives and the consent of many is based on the goal of achieving the desired outcome. MIS can be defined as a collection of systems, hardware, procedures, and people that all work together to process, store, and produce information that is useful to the organization. It is an important system for every organization that needs to have to ensure they remain competitive in the market. However, not all MIS fulfil the requirements from stakeholders. Some have failed to do so due to several factors such as poor requirement design or improper training to the users. Therefore, in this study, the paper focus to identify the key criteria that contribute to effectiveness in developing the “fit” MIS based on previous studies. The criteria discussed in detail by hoping this find out will become major guidelines to create a good MIS.